Paleomagnetic results from the Nain anorthosite and their tectonic implications - Murthy, G. S. (Canadian Journal of Earth Sciences, 1978)
As part of studies of anorthosites from the northern hemisphere, the paleomagnetism of the Nain anorthosite from Labrador is described. A total of 113 samples were collected from 21 sites comprising both dark and pale facies types. Although AF (alternating field) demagnetization was not useful in obtaining a stable component of magnetization, it was possible to isolate two oppositely directed (easterly and westerly) magnetizations through thermal demagnetization. Quite often, both magnetizations are found in the same specimen. On the basis of thermal demagnetization, the 18 sites of dark facies anorthosite are found to possess stable remanence at D = 278.2°, I = 15.8°, k = 174, α 95 = 2.6° with the corresponding paleomagnetic pole of mixed polarity at 11?N, 149°W (δ p , δ m = 1.5°, 3°). A magnetization with D = 275.3°, I = 27.2°, k = 92, α 95 = 12.9° with the corresponding paleomagnetic pole at 15°N, 148°W (δ p , [Formula: see text], 14°) was isolated for the pale facies anorthosite. Comparison of the Nain results with those of other plutons from Labrador suggests a significant difference in pole positions for the various anorthosite bodies north of the Grenville Front, which may represent a slight north–south polar shift during the time interval of intrusion of these bodies.